Ancient sites in Galilee : a toponymic gazetteer - Grootkerk, Salomon E. (Culture and history of the ancient Near East., 2000)
An inventory of all ancient sites now known in Galilee. The book is divided into 32 regions, each represented by a map. Each map has its sites numbered. The accompanying lists explain all sites chronologically, and identify the names the sites have carried in subsequent periods.